Colloidal Ni2−xCoxP nanocrystals for the hydrogen evolution reaction. Issue 24 (4th June 2018) - Liu, Junfeng; Wang, Zhenxing; David, Jeremy; Llorca, Jordi; Li, Junshan; Yu, Xiaoting; Shavel, Alexey; Arbiol, Jordi; Meyns, Michaela; Cabot, Andreu
Abstract : Ni2− x Co x P nanocrystals with controlled composition were produced and demonstrated to show excellent activity toward the hydrogen evolution reaction. Abstract : A cost-effective and scalable approach was developed to produce monodisperse Ni2− x Co x P nanocrystals (NCs) with composition tuned over the entire range (0 ≤ x ≤ 2). Ni2− x Co x P NCs were synthesized using low-cost, stable and low-toxicity triphenyl phosphite (TPP) as a phosphorus source, metal chlorides as metal precursors and hexadecylamine (HDA) as a ligand. The synthesis involved the nucleation of amorphous Ni–P and its posterior crystallization and simultaneous incorporation of Co. The composition, size and morphology of the Ni2− x Co x P NCs could be controlled simply by varying the ratio of Ni and Co precursors and the amounts of TPP and HDA. Ternary Ni2− x Co x P-based electrocatalysts exhibited enhanced electrocatalytic activity toward the hydrogen evolution reaction (HER) compared to binary phosphides. In particular, NiCoP electrocatalysts displayed the lowest overpotential of 97 mV at J = 10 mA cm −2 and an excellent long-term stability. DFT calculations of the Gibbs free energy for hydrogen adsorption at the surface of Ni2− x Co x P NCs showed NiCoP to have the most appropriate composition to optimize this parameter within the whole Ni2− x Co x P series. However, the hydrogen adsorption energy was demonstrated not to be the only parameter controlling the HER activity in Ni2− x Co x P.